Experiences of Caregivers and Students in an Elementary School–Based Mental Health Counseling Practicum Program. Issue 2 (2nd July 2016) - Solomon, Coralis; Bierbrauer, Samuel L.; Harris, Shaywanna; Belser, Christopher T.; Wheeler, Naomi J.; Crunk, A. Elizabeth; Lambie, Glenn W.
Abstract : School-based mental health counseling practicum programs are a potential solution to address the increasing social-emotional needs of underserved children and families. At present, little is known about how these school-based counseling practicum programs are experienced by elementary school students and their caregivers. Adopting a psychological phenomenological approach, the researchers examined the experiences of students (n = 6) and their caregivers (n = 6) receiving mental health counseling services in a Title I elementary school. The authors discuss the generated themes and implications.